2016
DOI: 10.1016/j.jtho.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Glasgow Prognostic Score as a Prognostic Factor in Resectable Non–Small Cell Lung Cancer

Abstract: A high GPS is significantly associated with poor OS. Although the biological mechanism that underlies this association is not clear, this inflammation-based score may be a useful indicator of the prognosis in patients with resectable NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 26 publications
6
48
1
Order By: Relevance
“…The GPS was both significantly related to DFS and OS in the univariate analysis. However, the GPS was not an independent predictive factor for both DFS and OS in the further multivariate analyses, which was different from the results of Yotsukura et al (). This may due to our smaller sample data or the addition of stage IIIA patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The GPS was both significantly related to DFS and OS in the univariate analysis. However, the GPS was not an independent predictive factor for both DFS and OS in the further multivariate analyses, which was different from the results of Yotsukura et al (). This may due to our smaller sample data or the addition of stage IIIA patients.…”
Section: Discussioncontrasting
confidence: 99%
“…It was first studied by Forrest et al as a new prognostic factor in patients with advanced NSCLC in 2003 based on the serum CRP and albumin levels (Forrest et al, ). In addition, Yotsukura et al () has shown that GPS is associated with survival of resectable stages I and II NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Initially used in advanced stage cancer patients, soon the two scores were used for a number of localized, resectable cancer as well [5254]. The GPS and the mGPS are simple to calculate and are supposed to reveal the host systemic immune and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that GPS as a solid prognostic factor in various tumors like Cervial cancer, non-small cell lung cancer, gallbladder cancer and advanced biliary tract cancer [25][26][27][28]. However, the study of GPS in lymphoma was relatively rare.…”
Section: Discussionmentioning
confidence: 99%